The Effect of Problem-Based Learning Model on Students’ Mathematical Literacy - Ekaputri, Hardianti; Simanjorang, Mangaratua M. (Interdisciplinary Social Studies, 2022)
Based on the interview results with one of the mathematics teachers at SMP Negeri 3 Medan, it was stated that students still lacked understanding of story problems, were less precise in identifying the information contained in the questions, and had difficulty in making mathematical models. Students' abilities in problem-solving and mathematical calculations are not maximal. The goal of this study was to establish if the problem-based learning model has affected students' mathematical literacy. The sample of this research was 15 students from class VII-J at SMP Negeri 3 Medan. This research was an experimental research with quasi-experimental methods using one group pre-test and post-test design. This study uses a test instrument that has been tested and is valid. The data on students' mathematical literacy abilities were tested for normality, and the results were normally distributed. Hypothesis testing was carried out using paired t-test. The results of this study at the significance level  showed that  then the alternative hypothesis was accepted, meaning that there was an increase in students' mathematical literacy skills after being given treatment. The explanation above can be concluded that there is an effect of problem-based learning on students' mathematical literacy skills at SMP Negeri 3 Medan.